Rainfall-runoff modeling and impact assessment of land parameters on water availability in Bisalpur reservoir, semi-arid Banas basin, Rajasthan, India - Agarwal, Sanjay Kumar; Munoth, Priyamitra; Sarkar, Archana; Goyal, Rohit (MAUSAM, 2025)
The accessibility of the water in the reservoir, particularly in semi-arid regions, holds paramount significance for the residents of the command and catchment areas. Situated in the semi-arid landscape of Rajasthan, India, the Bisalpur Dam plays a crucial role in providing drinking water to Jaipur, Ajmer, and Tonk districts, apart from catering to the command area’s agricultural needs. Knowing the water availability in the reservoir is important for the Water Resources Department (WRD) to optimise the utilisation of water resources and planning. Therefore, in this study, efforts have been made to model and predict inflow at Bisalpur Dam using the SWAT model. The calibration of the model was done for 2001-2008 with a warm-up duration of 2 years (2001-2002) and validated for 2009-2013 on a monthly scale. The performance indices like R2, NS, and PBIAS have been estimated, and the values were 0.90, 0.91, and 23.6% in calibration and 0.84, 0.70 and -20.6% in validation, respectively, which conclude that the model for the watershed fits successfully. The results show satisfactory model performance, and the Soil and Water Assessment Tool (SWAT) model effectively captured the dynamics of the Bisalpur watershed. As a result of this study, the most important land parameters that affect the water availability in the reservoir are related to soil characteristics such as permeability, soil evaporation, and deep aquifer percolation fraction. The developed model can be utilised for hydrological, land cover, land use, and climate change analysis of the Bisalpur watershed and may be replicated in other semi-arid areas after validation with the observed data.